Local Drug Delivery Strategies for Glioblastoma Treatment - Cha, Gi Doo; Jung, Sonwoo; Choi, Seung Hong; Kim, Dae-Hyeong (Brain tumor research and treatment, 2022)
Glioblastoma multiforme (GBM) is a brain tumor notorious for its malignancy. The key reason for the limited efficacy of standard treatment is the high recurrence rate of GBM, even after surgical resection. Hence, intensive postsurgical chemical therapies, such as the systemic delivery of various drugs and/or drug combinations, are typically followed after surgery. However, overcoming the blood-brain barrier by systemic administration to efficiently deliver drugs to the brain tumor remains a daunting goal. Therefore, various local drug delivery methods showing potential for improved therapeutic efficacy have been proposed. In particular, the recent application of electronic devices for the controlled delivery of chemotherapy drugs to GBM tissue has attracted attention. We herein review the recent progress of local drug delivery strategies, including electronics-assisted strategies, at the research and commercial level. We also present a brief discussion of the unsolved challenges and future research direction of localized chemotherapy methods for GBM.Glioblastoma multiforme (GBM) is a brain tumor notorious for its malignancy. The key reason for the limited efficacy of standard treatment is the high recurrence rate of GBM, even after surgical resection. Hence, intensive postsurgical chemical therapies, such as the systemic delivery of various drugs and/or drug combinations, are typically followed after surgery. However, overcoming the blood-brain barrier by systemic administration to efficiently deliver drugs to the brain tumor remains a daunting goal. Therefore, various local drug delivery methods showing potential for improved therapeutic efficacy have been proposed. In particular, the recent application of electronic devices for the controlled delivery of chemotherapy drugs to GBM tissue has attracted attention. We herein review the recent progress of local drug delivery strategies, including electronics-assisted strategies, at the research and commercial level. We also present a brief discussion of the unsolved challenges and future research direction of localized chemotherapy methods for GBM.